Bangladesh’s Flooding: Coping Strategies of Flood Affected People of Nageshwari Upazila - Sarker, Mehraz Hossain; Sujauddin, K. M. (American International Journal of Social Science Research, 2020)
Flood is one of the most common natural disasters in Southeast Asia, especially in Bangladesh. Extreme flood inundates more than half of the developing country’s landmass causing immense suffering to human life, damages properties, and economy. Furthermore, flood protection and management have been emphasized in terms of the sustainable development approach against climate impacts. As a result, Bangladesh has developed distinct indigenous practices to protect themselves from floods. The study aimed to identify the coping mechanisms and indigenous knowledge and the barriers to using these mechanisms. The study was conducted in two unions named Ratanpur and Nunkhawa of Nageshwari Upazila which is an Upazila of Kurigram District of Bangladesh. A mixed-method was used for the study. The survey questionnaire, focus group discussion (FGD) and key informants’ interviews (KII) were used as the tools for collecting data. Most of the respondents were farmers who had very minimal income level. Even though respondents used the shelter center during the flood incident, selling assents, letting children work, multiple works, extra labor were the fundamental strategies to overcome financial damage. The most common challenges faced by the victims to overcome the situation were the financial scarcity and recovering wasted crops. Filing to recover the vulnerability made some of the respondents migrate to another city or place. Proper money lending and credit system at reasonable or without interest rate, Instant food, and pure water supply can facilitate their mechanism.